Lost body corps perdu - Cesaire, Aime; Picasso, Pablo; Eshleman, Clayton; Smith, Annette (New York G. Braziller, 1986)
"The acclaimed Caribbean poet Aime Cesaire first came to public attention during the 1930s as the leading proponent of negritude, a philosophy that rehabilitates black culture, awareness and selfhood. It is these themes that are explored and developed in the series of poems entitled Lost Body, and it was just these themes that attracted Picasso to them. Fascinated by Cesaire's use of surrealist structures and metaphors that suggest black-African origins, the artist, for whom primitivism and surrealism had been equally important to his own development, sought to create a close visual equivalent. The spare lines and powerful textures of his etchings both activate, as well as are activated by Cesaire's language.The result is a splendid example of artistic collaboration by two of the century's most inventive minds." -- Provided by publisher
FA-2890g donated by Lewanda Lim, Ohio Gahanna.
Keywords: Poetry -- Collections; Poetry -- Women authors